The History of Dadi Temple from the Perspective of Cultural Experts and the Community of Wajak Kidul Village, Tulungagung Regency - Jaiyana Zahrani; Hendra Pratama (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2026)
Dadi Temple is a historical structure in Tulungagung Regency designated as a National‑level Cultural Heritage site. This study aims to explore and analyze the perspectives of cultural experts and the residents of Wajak Kidul Village concerning the history of Dadi Temple. The research employed a descriptive qualitative approach. Data were collected through in‑depth interviews with the temple’s caretakers, cultural experts, and local community members; architectural and environmental observations of the temple; and document analysis. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing and verification. Data validity was tested using methodological and source triangulation. Methodological triangulation compared findings from observation, interviews, and documentation, while source triangulation compared information from multiple informants to ensure the credibility of the results. The findings indicate that the periodization of Dadi Temple construction corresponds to the Majapahit era under the reign of King Hayam Wuruk in the 14th century CE, specifically toward the end of his rule. The functions of Dadi Temple included worship and ritual practice, ascetic retreat, and funerary cremation. In addition, the community preserves folklore concerning the temple’s origin that resembles the Prambanan legend. These findings demonstrate that Dadi Temple not only possesses historical value but also remains alive within the community’s collective memory through oral tradition. The diversity of perspectives on Dadi Temple illustrates that history is not merely a record of past facts but also a product of interpretation and collective memory transmitted across generations.